Asymmetric response to monetary policy surprises at the long-end of the yield curve - Selva Demiralp; Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2009)
This paper provides a dynamic analysis of the responsiveness of asset markets to monetary policy path revisions. In an era of increased transparency and gradualism in policy making, one might expect an increased response to path revisions in asset markets as the policy actions become more predictable over longer horizons. Using federal funds futures contracts to extract near-term path revisions, we find that the responsiveness of Treasury securities to path revisions is significantly asymmetric, increasing during cycles of tightenings and declining during easings. This is consistent with the earlier literature that documents asymmetric effects of monetary policy on output.
Keywords: E44; E52; 330; asymmetric monetary policy; yield curve; federal funds futures; Geldpolitik; Transmissionsmechanismus; Finanzmarkt; Pfadabhängigkeit; Öffentliche Anleihe; Volatilität; Welt